1994
DOI: 10.1210/edrv-15-6-788
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Thyroid Disease: Further Developments in Our Understanding*

Abstract: The revolution in molecular techniques has allowed dissection of the autoimmune response in a way impossible to imagine 10 yr ago. There have been spectacular advances in our understanding of self-tolerance mechanisms and how these may fail, combined with a detailed comprehension of antigen presentation, functional T cell subsets, and TCR utilization in autoimmunity, albeit usually in animal models that resemble, but do not exactly duplicate, human diseases. More gradually, these findings are being translated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
160
1
15

Year Published

1996
1996
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(178 citation statements)
references
References 339 publications
2
160
1
15
Order By: Relevance
“…H-2S and H-2q have been reported to be high-responder strains in terms of their levels of anti-TSHR antibodies when immunized with soluble human TSHR (5). This possibility would be consistent with the prevalence of certain HLA haplotypes (B35) in GD but not Hashimoto thyroiditis (31 (19)(20)(21), its biological significance has never been systematically examined and shown to be a primary causative factor, rather than a factor secondary to cytokine production by invading immune cells (22). A recent report by Sopedra et al (33), which showed the hyperinducibility of HLA class II expression in thyroid follicular cells from patients with GD, supports a possible role for class II molecules in the development of GD; our present data directly implicate aberrant class II expression as a potential causal factor in the development of stimulating TSHRAbs.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…H-2S and H-2q have been reported to be high-responder strains in terms of their levels of anti-TSHR antibodies when immunized with soluble human TSHR (5). This possibility would be consistent with the prevalence of certain HLA haplotypes (B35) in GD but not Hashimoto thyroiditis (31 (19)(20)(21), its biological significance has never been systematically examined and shown to be a primary causative factor, rather than a factor secondary to cytokine production by invading immune cells (22). A recent report by Sopedra et al (33), which showed the hyperinducibility of HLA class II expression in thyroid follicular cells from patients with GD, supports a possible role for class II molecules in the development of GD; our present data directly implicate aberrant class II expression as a potential causal factor in the development of stimulating TSHRAbs.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, several studies have implicated class I as an important component in the development of autoimmune thyroid disease and in the action of methimazole, a drug used to treat GD (14)(15)(16)(17)(18). In addition, aberrant class II expression, as well as abnormal expression of class I molecules, is evident on thyrocytes in autoimmune thyroid diseases (19)(20)(21), although the cause and role of aberrant class II in disease expression remains controversial (22). The sum of these observations raised the possibility that immunization with full-length TSHR, in a functional conformation but in the context of abnormal MHC class I or class II expression, might lead to the development of GD.…”
mentioning
confidence: 99%
“…However, despite their contrasting clinical presentations, GD and HT share many features in common, mainly, infiltration of the thyroid by T cells and production of antithyroid autoantibodies [antithyroglobulin and anti-thyroid peroxidase (TPO) antibodies] (3)(4)(5). AITDs are complex diseases, which are caused by an interaction between susceptibility genes (6)(7)(8) and nongenetic factors, such as infection (9)(10)(11)(12). This paradigm is based on solid epidemiologic evidence demonstrating a genetic predisposition to AITDs, including: (i) familial clustering (13); (ii) a sibling risk ratio ( s ) of Ͼ10 (7,14); (iii) a high concordance rate in monozygotic twins when compared with dizygotic twins (15)(16)(17)(18); and (iv) the presence of thyroid autoantibodies, which are markers of subclinical AITD, in up to 50% of siblings of patients with AITD (19,20).…”
mentioning
confidence: 99%
“…Many studies have shown that IL-8 participates in many diseases such as bronchial asthma, multiple sclerosis, systemic sclerosis, and psoriasis. GD, with the thyroid as a major target for autoimmunity, is characterized by reactivity to self-thyroid antigens and by lymphocyte infiltration of the gland [27][28][29][30]. Although the etiology of GD remains unclear, it is believed to be caused by a complex interaction between genetic and environmental factors.…”
Section: Rs2227306 In Il-8 Gene Association Between Graves' Ophthalmomentioning
confidence: 99%